Prospective Analysis of Risk for Hypothyroidism after Hemithyroidectomy. (30th March 2015) - Beisa, Virgilijus; Kazanavicius, Darius; Skrebunas, Arminas; Simutis, Gintaras; Ivaska, Justinas; Strupas, Kestutis
Abstract : Objectives . To evaluate risk factors and to develop a simple scoring system to grade the risk of postoperative hypothyroidism (PH). Methods . In a controlled prospective study, 109 patients, who underwent hemithyroidectomy for a benign thyroid disease, were followed up for 12 months. The relation between clinical data and PH was analyzed for significance. A risk scoring system based on significant risk factors and clinical implications was developed. Results . The significant risk factors of PH were higher TSH (thyroid-stimulating hormone) level and lower ratio of the remaining thyroid weight to the patient's weight (derived weight index). Based on the log of risk factor, preoperative TSH level greater than 1.4 mU/L was assigned 2 points; 1 point was for 0.8–1.4 mU/L. The derived weight index lower than 0.8 g/kg was assigned 1 point. A risk scoring system was calculated by summing the scores. The incidences of PH were 7.3%, 30.4%, and 69.2% according to the risk scores of 0-1, 2, and 3. Conclusion . Risk factors for PH are higher preoperative TSH level and lower derived weight index. Our developed risk scoring system is a valid and reliable tool to identify patients who are at risk for PH before surgery.